ENHANCING READING COMPREHENSION SKILLS IN ENGLISH LANGUAGE TEACHING FOR VOCATIONAL SCHOOL STUDENTS: METHODOLOGICAL APPROACHES (American Journal of Research in Humanities and Social Sciences, 2024)
This scientific article explores effective methodologies for teaching reading comprehension skills in English language instruction for students in vocational schools. Reading comprehension is a fundamental skill that plays a crucial role in language acquisition and vocational success. Drawing upon educational research and pedagogical practices, this study examines various methodological approaches to improve reading comprehension abilities in vocational school students. It discusses strategies for pre-reading, during-reading, and post-reading activities, as well as the integration of authentic materials, technology, and critical thinking. The article concludes by emphasizing the importance of a learner-centered approach and the need for continuous professional development for English language teachers in vocational schools.